2011
DOI: 10.6004/jnccn.2011.0116
|View full text |Cite
|
Sign up to set email alerts
|

Effort Tracking Metrics Provide Data for Optimal Budgeting and Workload Management in Therapeutic Cancer Clinical Trials

Abstract: Clinical trials operations struggle to achieve optimal distribution of workload in a dynamic data management and regulatory environment, and to achieve adequate cost recovery for personnel costs. The University of Michigan Comprehensive Cancer Center developed and implemented an effort tracking application to quantify data management and regulatory workload to more effectively assess and allocate work while improving charge capture. Staff recorded how much time they spend each day performing specific study-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…Such activities have been found to present barriers in other clinical trials management examinations , with implications for successful trial implementation and completion. Dealing with multiple IRB reviews , meeting accrual sufficiency , recruitment and retention, generally and of minority populations specifically , budgeting and cost allocation , and results dissemination have all been identified as potential barriers in the clinical trials literature and have been shown to impact successful clinical trials outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Such activities have been found to present barriers in other clinical trials management examinations , with implications for successful trial implementation and completion. Dealing with multiple IRB reviews , meeting accrual sufficiency , recruitment and retention, generally and of minority populations specifically , budgeting and cost allocation , and results dissemination have all been identified as potential barriers in the clinical trials literature and have been shown to impact successful clinical trials outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Over a 4-year period, the data obtained from use of this tool have not only assisted with workload management, trial budget development, and cost recovery, but have also compelled the group to think critically about clinical trials management and enabled them to identify the most complex and time-consuming tasks that affect the bottom line. A subsequent article 6 provides an analysis of the data yielded and discusses trial characteristics and the impact of those characteristics on workload and resource allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, one was a quality improvement study (Cusack et al, 2004a(Cusack et al, , 2000bJones et al, 2004) and two were expert opinion or commentary (Cassidy & Macfarlane, 1991;Smuck et al, 2011). In relation to psychometric assessments, eight had no reliability and validity data reported (Berridge et al, 2010;Ellis et al, 2012;Good et al, 2013;Gwede et al, 2000aGwede et al, , 2000bJames et al, 2011aJames et al, , 2011bMcCarthy, 1997;Roche et al, 2002;Smuck et al, 2011). Five studies mentioned reliability and validity but no data were presented (Briggs, 2008;Coffey et al, 2011;Cusack et al, 2004aCusack et al, , 2000bJones et al, 2004;Oddone et al, 1995;Penberthy et al, 2012).…”
Section: Acuity Tools Pertaining To Research Intensitymentioning
confidence: 99%